Digital examination question paper maker and analyser / Eng Cheng Kait - Eng , Cheng Kait (2004)
For the past few years, the increased numbers of student in education institution make it more time consuming to evaluate the student assessments. ln order to reduce the teaching staff's workload, they must be either set fewer assessment tasks or propose some possible solutions to save time and energy. Following from those reasons, Digital Examination Question Paper Maker & Analyzer have been developed to achieve these objectives. The system has provided the functionalities for lecturers easily organize, mark, and analyze their assessment papers. Besides, it's also to serve the purpose of providing a secure online examination which allows students sit for the examination by accessing the web-based system. The results from student will be further analyzed by system and displayed in various forms of report. The waterfall model with prototyping has been chosen to be the methodology in developing the system. Functional and non-functional requirements is stated clearly early the development process for the purpose to controlling and monitoring in the future. System architecture design, system functionality design, database design and user interface design are used to develop the prototyping before the system is completed. After all the technologies have reviewed and analyzed, ASP.Net is selected in the system development because of its powerful feature and complete architecture for developing Web sites.